Kontynuacja czy nowy start? Inteligencja techniczna w powojennym przemyśle motoryzacyjnym (1945–1970) - Wilk, Hubert (Komunizm: System - Ludzie - Dokumentacja, 2023)
After the end of warfare, the new political power in Poland faced a dilemma over the direction of the development of motorisation and the automotive industry. The legacy of the Second Polish Republic was modest. Only in the second half of the 1930s, the people in power decided – in the face of a military threat from the neighbours – to develop the industry faster; before, they had utterly ignored automotive backwardness of the country. Unfortunately, the outbreak of the Second World War and the consequences of the Nazi, as well as the Soviet, occupation policies meant that the automotive industry had to start almost from scratch. Nearly all motor vehicles that had roamed the Polish roads in September 1939 were destroyed. Road infrastructure had been devastated, just like the plants and factories of the automotive industry, including the documentation of manufactured vehicles and sub-assemblies. Thus, the new authorities decided to rely on technical and engineering staff. The majority of the pre-war engineers and technicians working in the automotive industry survived the war. Most of the large group of technical intelligentsia decided to join the process of rebuilding the domestic automotive industry, regardless of their political beliefs. As a consequence, the production of trucks, passenger cars, and tractors started in Poland. The technical staff of Fabryka Samochodów Osobowych [Passenger Automobile Factory] predominantly comprised pre-war automotive industry employees. At the same time, academics who had worked before the war at technical universities in Warsaw, Lviv, and the AGH University of Science and Technology in Kraków started teaching at newly created technical universities, providing continuity between this period and the Second Republic of Poland. The new technical staff trained for the automotive industry had direct contact with people who remembered 1918–1939 years very well.